"Shadowing" of the electromagnetic field of relativistic charged particles; Arxiv.org - Naumenko G. A. Gennadiy Andreevich; Artru X.; Potylitsyn A. P. Alexander Petrovich; Popov Yu. A. Yuriy Anatolevich; Sukhikh L. G. Leonid Grigorievich; Shevelev M. V. Mihail Viktorovich (2009, 2009)
Title screen